The Risk Assessment of Earthquake on Historical Structures and Monuments - Tiwari, Pankaj Kumar (PREPARE@u® | IEI Conferences, 2021)
This paper discusses the risk assessment of earthquake on historical structures and monuments as per their height and shape with reference to the earthquake that occurred on 25 April 2015 and on 12 May 2015. Heritage Site, Dharahara tower, which was very high-rise in height, totally collapsed. Owing to such height the upper portions of 9-storied Basantapur Durbar, the Dasa Avtar temple were demolished by the quake. In an earlier earthquake in India near Aravali hill range in 1505, damaged Qutub Minar, Delhi built in 12th century, was fallen off its top two story, after like some quake due to sky/cloud bursting electric happening, but no such damage to ground, first and second story structures was noticed. Generally many old forts in India, were safe during earthquakes due to large in plan area and low in height , but further the high-rise old buildings suffered during earthquake at some specific intensity of earthquake at several times in past . It is important to point out the height and shape of historical structures and monuments for further safety measures and precautions as for as possible for load bearing structures, in Zone V with less than 400 sqm (appox.) in plan area of foundation with plinth may be risk affected during/after earthquake.